Levetiracetam-induced neutropenia following traumatic brain injury. (January 2015) - Bunnell, Kristen; Pucci, Francesco
Abstract Background: Levetiracetam is being increasingly utilized for post-traumatic brain injury seizure prophylaxis, in part because of its more favourable adverse effect profile compared to other anti-epileptics. This report highlights an unusual, clinically significant adverse drug reaction attributed to levetiracetam use in a patient with blunt traumatic brain injury. Methods: This study describes a case of isolated neutropenia associated with levetiracetam in a 52-year-old man with traumatic brain injury. Results: The patient developed neutropenia on day 3 of therapy with levetiracetam, with an absolute neutrophil count nadir of 200. There were no other medications that may have been implicated in the development of this haematological toxicity. Neutropenia rapidly resolved upon cessation of levetiracetam therapy. Conclusions: Clinicians should be aware of potentially serious adverse reactions associated with levetiracetam in patients with neurological injury.